成人1型糖尿病患者幸福感和HbA1c之间的关系:一项系统综述 - Aida Pérez‐Fernández; Pablo Fernández‐Berrocal; María José Gutiérrez‐Cobo (Journal of Diabetes, 2023)
Abstract Background Diabetes has been associated with psychological problems, which in turn have been related to poorer glycemic control (glycosylated hemoglobin [HbA1c]). On the contrary, psychological well‐being constructs have been associated with superior medical outcomes, including better HbA1c. Aim The main objective of this study was to systematically review the existing literature about the relationships between subjective well‐being (SWB) and HbA1c in adults with type 1 diabetes (T1D). Methods Comprehensive searches were conducted in PubMed, Scopus, and Medline, time restricted to 2021, for studies examining the link between HbA1c and the cognitive (CWB) and affective (AWB) components of SWB. A total of 16 eligible studies were selected according to the inclusion criteria, of which 15 measured CWB and 1 AWB. Results Of the 15 studies included, 11 showed a relationship between CWB and HbA1c, with a higher level of HbA1c being related to poorer CWB. The other four studies did not find any significant association. Finally, the only study examining the relationship between AWB and HbA1c found a marginally association between these variables in the expected direction. Conclusion The overall data suggest that CWB is negatively related to HbA1c in this population, but these results are inconclusive. This systematic review offers clinical implications, such as the possible evaluation, prevention, and treatment of the problems associated with diabetes through the study and training of the psychosocial variables that may directly influence SWB. Limitations and future lines of investigation are discussed.